Management Control System Backbone in a CPA Firm: Middle Managers and the Power of Cultural Control - Jesslyn Elaine Saputra; Sujoko Efferin (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This research aims to broaden the understanding of the middle manager's role in the management control system, particularly in mediating the relationship between superiors and subordinates. The methods employed in this research are an interpretive paradigm with interview, observation, and document analysis data collection methods. Findings indicate that middle managers at the CPA X play a crucial role in addressing ignorance, inability, and unwillingness in the company. Although there are no formal controls, role dissonance among middle managers is minimal due to the presence of strong cultural controls. Cultural control can compensate for other forms of control, thus minimizing the occurrence of role dissonance experienced by the manager of CPA Firm X. This research provides insight into the importance of middle managers' role in fulfilling their function as an intermediary in the management control system aimed at aligning the goals of top management with operational employees.